Leg placement algorithm for foot impact force minimization. (16th January 2018) - Luneckas, Mindaugas; Luneckas, Tomas; Udris, Dainius
Walking is considered to be a rather complicated task for autonomous robots. Sustaining dynamic stability, adopting different gaits, and calculating correct foot placement are a necessity to overcome irregular terrain, various environments and completing a range of assignments. Besides that, certain assignments require that robots have to walk on fragile surfaces without damaging it. Furthermore, under some other circumstances, if walking is careless, robots could suffer damage caused by the impact of the terrain. Foot placement, leg motion speed must be controlled to avoid braking surface or even sensors on robot's feet. In this article, a simple leg placement algorithm is proposed that controls hexapod robot's leg speed. Thus, force dependence on leg motion speed and step height has been measured by using a piezoelectric sensor. Then, by using leg placement algorithm, we show that the reduction of the impact force between robot's foot and surface is possible. Using this algorithm, robot feet's impact force with the surface can be minimized to almost 0 N.